Observation of ferromagnetic phase in the second moiré band of twisted MoTe2 - Liheng An; Haiyang Pan; Wen-Xuan Qiu; Naizhou Wang; Shihao Ru; Qinghai Tan; Xuran Dai; Xiangbin Cai; Qiuyu Shang; Xiufang Lu; Hao Jiang; Xiaodan Lyu; et al. (Nature Communications)
Abstract Flat bands and electron correlation in moiré lattices give rise to many exotic phases, including Mott insulators, superconductivity, and topological states. Within the first moiré band, integer and fractional quantum anomalous Hall effects have been observed in twisted bilayer MoTe2 (tMoTe2) at one hole doping and fractional doping per moiré unit cell, respectively. When the second moiré band is fully hole doped, quantum spin Hall insulator has also been reported in tMoTe2 at a certain twist angle. Exotic topological states together with ferromagnetic (FM) states in the high moiré band can potentially exist as well. In this study, we report the observation of a FM phase in the second moiré band in tMoTe2. The FM phase can be tuned by both the doping level and displacement field. At filling around 2.58 holes per moiré unit cell, the FM phase reaches a Curie temperature of 3.5 K. A large displacement field can suppress the FM phase, like the FM phase at the filling of −1. Our results demonstrate the realization of time-reversal symmetry-breaking states in the higher moiré bands in tMoTe2.